Penerapan Tata Kelola Islam Dalam Perbankan Syariah Di Indonesia: Sebuah Studi Kepustakaan - Laksita Sela Srimaya; Elsa Amalia (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine how the application of Islamic governance in Sharia banking, especially in Indonesia. The approach used in this study is a qualitative approach by applying library research methods. The data used in this study is secondary data which are books and articles related to the topics discussed taken from accounting journals. The development of the Sharia banking industry can be seen from the increasing variety of Sharia banking products and the growing network of Sharia banking services. The results of literature study indicate that with the development of Sharia banking, governance in the Sharia banking industry is becoming increasingly important to implement. The importance of Islamic governance occurs through its role in ensuring and maintaining the trust of the Sharia banking and finance industry from the perspective of its stakeholders. This study shows that the application of Islamic governance in Indonesia is regulated by Bank Indonesia Regulations. Indonesian Sharia Banking must be guided by various provisions and requirements related to the implementation of governance and must comply with sharia principles. However, in general, Sharia Banking in Indonesia is still unable to implement Islamic governance in its daily operational activities.